Impact of the RF front end on the out-of-band interference performance - Lim, Vivian Jun Xian. (2013)
The Out-Of-Band response of a generic wire antenna, such as a simple monopole, has been analyzed using different antenna models. Our study showed that the low frequency gain roll off is about 55 dB/decade for wire type antenna. Across the rest of the OOB frequency band, the analytical and simulated antenna models also showed good agreement with the measured results. The main contributors for the OOB gain response for these classes of antenna are mainly due to its directivity and mismatch loss. In this report, it will be showed that certain two-element matching topology have a better OOB performance when compared to other. By simply switching to a three-element network, the matchable frequency bandwidth of our matching unit can be increased without sacrificing its OOB performance.